Latin American Foreign Policy before the hegemony of the United States and China's emerging power - Zapata Mafla, Sandra; Martínez-Hernández, Aldo Adrián (Colombia Internacional, 2020)
Objective/Context: Drawing on the analytical framework of the reconfiguration of international power, this article seeks to analyze and explain the political alignment of Latin American countries towards the great powers from the perspective of a triangular relationship: Latin America, the United States, and China. The aim is to empirically test the hypothesis that the increasingly assertive presence of the Asian country in the region since the year 2000 shapes new political alignments in its favor. Methodology: We examined the resolutions adopted by 19 Latin American countries from 1970 to 2015 at the UNGA and focused on three specific periods: bipolarity (1976-1991), unipolarity (1992-2002) and multipolarity (2003-2015). Our research combines the quantitative method with statistical analyses as it seeks to compare and explain the factors that determine foreign policy. Conclusions: The results suggest that domestic factors, political cycles, periods of global polarity, and economic conditions determine political convergences that are closer to China than to the United States. This enables defining how the group of countries, with coinciding characteristics, align themselves in relation to the two powers analyzed. Originality: The research promotes a quantitative approach to the study of International Relations, specifically to the analysis of Foreign Policy. The linkage of the theoretical foundations of neorealism with the methodological strategy that quantitatively identifies systemic and domestic variables provides a consistent model that allows us to characterize the conditions in which Latin American countries establish their foreign policy decisions. These elements, along with the descriptive and explanatory findings, show the originality of the research with respect to the state of the art in the subject.
CRIS-Team Scopus Importer:2021-04-19
Keywords: China; Foreign policy; Latin America; UNGA; United States